A SYSTEMATIC REVIEW OF THE ADVANCE NURSE PRACTITIONER MODEL BARRIERS AND STRATEGIES TO INITIATE IN PAKISTAN (The Research of Medical Science Review, 2025)
This study aims to identify the barriers preventing the implementation of the Advanced Nurse Practitioner (ANP) model in Pakistan and explore strategies for its successful integration. The ANP model has proven to enhance healthcare accessibility, optimize clinical efficiency, and improve patient outcomes globally. However, Pakistan faces challenges such as regulatory gaps, insufficient leadership opportunities, unclear role definitions, and limited advanced nursing education pathways. To address these issues, a systematic review was conducted, analyzing existing research, policy documents, and case studies. Comparisons were drawn with internationally recognized ANP models to provide evidence-based insights and recommendations. Data were analyzed to categorize barriers and enablers across four structural levels: healthcare system, organizational, team, and practitioner levels. The review highlights significant barriers in Pakistan, including the absence of national accreditation frameworks, inadequate leadership training, unclear role boundaries, and resistance from medical professionals. Globally, successful ANP models in countries such as the U.S., UK, Canada, and Australia demonstrate the importance of structured education programs, clear regulatory frameworks, and leadership opportunities for ANPs. These models emphasize the role of mentorship programs, interdisciplinary collaboration, and administrative support in overcoming challenges. The findings suggest that addressing these barriers through policy reforms, leadership development, and institutional support will facilitate the integration of the ANP model in Pakistan. This integration is critical for strengthening the nursing workforce, improving healthcare service delivery, and ensuring better patient outcomes. By learning from global best practices, Pakistan can establish a sustainable ANP model to meet its growing healthcare demands.